(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: Depression is a state of low mood and aversion to activity that can affect a person’s thought, behavior feelings and physical wellbeing. Mental health of adolescents has been drawn going attention due to sustain increase in adolescent depression as well as suicidal incidence. The study aimed to determine the level of depression among the urban adolescents and its association with socio-economic status (SES). Methods: A descriptive cross-sectional study was carried out among 384 adolescent students of selected English and Bangla medium school of Dhaka city during January to December 2016. A semi-structured questionnaire and convenience sampling technique were used for data collection. Data were analyzed using SPSS software. Results: The study findings revealed that a large number of adolescents (34.11%) had depression and females are more (80%) prone to be depressed. Socio-economic status had significant association with the level of depression (p- 0.000). Out of 131 depressed respondents, 58.77%, 28.24%, 12.97% were in middle, upper and lower class respectively. Among all the depressed adolescents, 67.93% found significant depression and (32.06%) found cutoff score of depression. Conclusion: This study showed that depression is remained uncared health problem among the adolescents due to socio-economic problem. More attention and awareness need at the national level for early diagnosis of Adolescent depression. JOPSOM 2020; 39(1): 21-25